Inside creative writing : interviews with contemporary writers (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
High profile writers, including Philip Pullman, Nadine Gordimer, Kate Grenville and Robert Pinsky, talk about their writing practice and ways of working. Designed with the needs of creative writers in mind, Graeme Harper explores both practice and process, asking authors questions about subjects ranging from motivation to creativity to drafting.
Includes index
Keywords: Creative writing; Authorship